Pemberian Jus Jambu untuk Mencegah Perdarahan pada Anak dengan DHF dan Trombositopenia Di Ruang Cendana I RSUD Kardinah Tegal : Studi Kasus - Indriani, Eka Susi; Murniati, Murniati; Mulyani, Sri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Dengue Hemorrhagic Fever (DHF) is commonly transmitted through mosquitoes infected with the dengue virus. The most feared infection of the dengue virus is bleeding. The risk of bleeding can be overcome by giving red guava juice to increase the patient's platelets. Red guava is classified as a fruit that has significant nutritional content, especially essential vitamins and minerals that play an important role in supporting the physiological functions of the body. The high vitamin C content in this fruit contributes to improving the body's immunity. Furthermore, vitamin C intake from red guava plays a role in stimulating the thrombopoiesis process, which is the formation of new blood platelets. This case study aims to describe the effectiveness of guava juice administration in Dengue Haemorrhagic Fever patients with Thrombocytopenia in Cendana I Room, Kardinah Tegal Hospital. The case study was conducted by observation for 3x meetings and intervention of guava juice for 3 days on April 24-26, 2025. The results of the case study on the first day of the patient's platelets before being given guava juice therapy were 106/mm3, on the second day there was an increase to 138/mm3and on the third day there was a significant increase to 246/mm3. In conclusion, guava juice therapy is effective in increase platelet levels in Dengue Haemorrhagic Fever with Thrombocytopenia in Cendana I Room, Kardinah Tegal Hospital.